Pengaruh Model Pembelajaran Kooperatif Tipe Think-Pair-Share terhadap Hasil Belajar dalam Menulis Teks Eksposisi Siswa Kelas VIII di SMP Negeri 2 Rumbia Kabupaten Jeneponto - Utami, Darmayanti Mauti; Idawati, Idawati; Hajrah, Hajrah (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to describe the effect of the Think-Pair-Share (TPS) cooperative learning model on students' learning outcomes in writing expository texts at SMP Negeri 2 Rumbia, Jeneponto Regency. This study uses a quantitative approach with a quasi-experimental design and a pretest-posttest control group design. The instruments used are written tests, both multiple choice and essay. The research sample was 42 students who were divided into an experimental class and a control class. The results showed that the implementation of the Think-Pair-Share model significantly improved student learning outcomes. The average score of students in the experimental class increased from 32.71 in the pretest to 63.19 in the posttest, with the results of the paired sample t-test showing a sig. 0.000 < 0.05. In addition, there was a significant difference between the experimental class and the control class based on the independent sample t-test (sig. 0.000 < 0.05). Thus, the Think-Pair-Share learning model proved more effective than conventional methods in improving students' expository writing skills at SMP Negeri 2 Rumbia, Jeneponto Regency.